Feminist Theory, Agency, and the Liberatory Subject: Some Reflections on the Islamic Revival in Egypt - Mahmood, Saba (Temenos, 2006)
This article argues that insomuch as feminism is both an analytical and politically prescriptive project, it aims not only to analyze the situation of women in different historical and cultural locations but also to transform their conditions of subjugation. Consequently, feminist scholarship tends to accord freedom a normative status, and to emphasize those instances that exemplify women's desire to be free from relations of subordination. An important consequence of this tendency in feminist scholarship is to limit the conceptualization of agency to acts that further the moral autonomy of the individual in the face of power. Through an examination of the women's piety movement in Egypt, this article argues for uncoupling the notion of agency from that of resistance as a necessary step in thinking about forms of desire and politics that do not accord with norms of secular-liberal feminism and its liberatory telos.